Proceedings of the Workshop on Deep Learning Approaches for Low-Resource NLP 2018
DOI: 10.18653/v1/w18-3403
|View full text |Cite
|
Sign up to set email alerts
|

Multi-task learning for historical text normalization: Size matters

Abstract: Historical text normalization suffers from small datasets that exhibit high variance, and previous work has shown that multitask learning can be used to leverage data from related problems in order to obtain more robust models. Previous work has been limited to datasets from a specific language and a specific historical period, and it is not clear whether results generalize. It therefore remains an open problem, when historical text normalization benefits from multi-task learning. We explore the benefits of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Data. We experiment on the ten datasets from Bollmann et al (2018), which represent eight different languages: German (two datasets; Bollmann et al, 2017;Odebrecht et al, 2017); English, Hungarian, Icelandic, and Swedish (Pettersson, 2016); Slovene (two datasets; Ljubešic et al, 2016); and Spanish and Portuguese (Vaamonde, 2015). We treat the two datasets for German and Slovene as different languages.…”
Section: Historical Text Normalization (Norm)mentioning
confidence: 99%
See 3 more Smart Citations
“…Data. We experiment on the ten datasets from Bollmann et al (2018), which represent eight different languages: German (two datasets; Bollmann et al, 2017;Odebrecht et al, 2017); English, Hungarian, Icelandic, and Swedish (Pettersson, 2016); Slovene (two datasets; Ljubešic et al, 2016); and Spanish and Portuguese (Vaamonde, 2015). We treat the two datasets for German and Slovene as different languages.…”
Section: Historical Text Normalization (Norm)mentioning
confidence: 99%
“…Both encoder and decoder have a single hidden layer. We use the default model in Open-NMT (Klein et al, 2017) 3 as our implementation and employ the hyperparameters from Bollmann et al (2018). In the original paper, early stopping is done by training for 50 epochs, and the best model regarding development accuracy is applied to the test set.…”
Section: Historical Text Normalization (Norm)mentioning
confidence: 99%
See 2 more Smart Citations
“…One active research question however is what information in specific tasks should be shared, as well was what indicators can be used to predetermine the cost-benefit trade-offs of MTL for a given application. Findings have shown that label distributions (Martínez Alonso and Plank, 2017), data sizes (Bollmann et al, 2018) and single task loss curves (Bingel and Søgaard, 2017) have all been respective indicators for MTL performance. Different tasks, data sizes, and settings can all show different relative performance gains (Adouane and Bernardy, 2020).…”
Section: Introductionmentioning
confidence: 99%